Psychological and Pedagogical Foundations of Teaching Students the Russian Language as a Foreign Language using Computer Technology - Rakhimov, Bakhtiyor Khudoyberdievich; Nurmukhamedova, Dilbar Farukhovna; Jonzakova, Sayyora Anvarovna; Buriev, Ilkhamdjan Ergashevich; Khidirova, Malokhat Kazakovna (International Journal of Psychosocial Rehabilitation, 2020)
This article is written to theoretically substantiate the psychological and pedagogical foundations of teaching students the Russian language as a foreign language using computer technology. The following tasks are identified and solved in the article: to analyze the state of ICT use in the work of teachers of the Russian language in universities; to identify the pedagogical goals of using ICT tools in the process of teaching the Russian language in a personality-oriented approach; to determine the requirements for the structure, content of educational material and the organization of educational activities using ICT in Russian language lessons; to develop and experimentally verify the effectiveness of pedagogical conditions for using ICT tools in improving the quality of teaching the Russian language at a university.